To Study the Computed Tomography Temporal Bone Findings inPatients with Chronic Suppurative Otitis Media - Priyanka Manda; Ratna Vasanthan; Krishna Kumar; Velayutham Prabu; Govardhanan (International Journal of Medical Research and Review, 2022)
Background: Chronic suppurative otitis media is a chronic inflammation of middle ear cleft. It canpresent with discharging ear and decreased hearing. Diagnosis is mostly on clinical examination withan otoscope or otoendoscope. Our study was undertaken to evaluate role of computed tomographyin defining extent and severity of various pathological changes occurring in temporal bone in case ofchronic suppurative otitis media. Materials and Methods: Current study was a prospective cross-sectional study was conducted in Sri Venkateshwaraa Medical College and Research Center, Ariyur,Pondicherry from January 2019 to May 2020. Study included 60 patients clinically diagnosed with achronic middle ear infection and who were referred to Department of Radiodiagnosis and Imaging foran HRCT scan of temporal bone. All obtained data were entered in Microsoft Excel and analyzed withSPSS 23.0 software. Results: In our study, a total number of 60 patients were involved. Youngestpatient was aged 7 years and oldest patient’s age was 63 years. Majority (28.33%) of patients wereaged between 21-30 years followed by 26.67% in 11-20 years age group. Our study found site andextent of involvement of middle ear and mastoid air cell system as follows: protympanum (20.00%);meso-tympanum (26.67%); posterior tympanum (30.00%); epitympanum (60.00%); hypo-tympanum (25.00%); peri-labyrinthine cells (1.67%); aditus (53.33%); antrum (40.00%); mastoidair cells (58.33%). Conclusion: HRCT scan is a unique method to detect early cholesteatoma andalso to detect cholesteatoma in hidden areas.